THE ROLES OF CADRE AS A SUPPORT GROUP FOR PEOPLE WHO LIVING WITH HIV/AIDS - Niko Dima Kristianingrum; Annisa Wuri Kartika; Yati Sri Hayati; Kumboyono Kumboyono Kumboyono; Nurul Aisyah Puspitarini (Caring : Jurnal Pengabdian Masyarakat, 2022)
The people living with HIV (PLWH) are vulnerable population with several health problems and stigma from the community. People living with HIV need social support from the people around them, include community health worker as support groups. The purpose of this activity was to increase the knowledge and attitude of cadre as support group in providing support to PLWH. This program consists of health education and training as support group for PLWH. The target of the activity was 20 community health workers in Turen district, Malang Regency. The activity was held on October 16, 2021. Participants were given a knowledge and attitude questionnaire before and after the activity. The results of the paired t test about community health worker knowledge obtained a value of 0.000 (<p value 0.05) so it means there was a significant difference between the average level of pre-test and post-test cadre knowledge. The results of the paired t test about community health worker attitudes obtained a value of 0.000 (<p value 0.05) so it menas that there is a significant difference between the average of pre-test and post-test community health worker attitudes. It can be concluded that support group training can improve the knowledge and attitudes of community health worker as support group for PLWH.